Canine & feline endocrinology - Feldman, Edward C.; Nelson, Richard W. 1953-; Reusch, Claudia; Scott-Moncrieff, J. Catharine R. (Elsevier/Saunders, 2015)
No other title offers such dedication to the depth, experience, and focus of endocrinology as Canine and Feline Endocrinology, 4th Edition. Comprehensive coverage includes virtually every common and uncommon condition in endocrinology, plus the most updated information on nutrition, geriatric care, pathophysiology, testing procedures, and cost-effective and expedient diagnostic protocols. With its logical, step-by-step guidance for decision making, diagnosis, and prescribing, you will be well-equipped to care for the wide spectrum of endocrine and metabolic disorders in dogs and cats